Quantitative and qualitative influences of spiritual connection and natural imagery on perception of art in clinical psychedelic dosing settings - Suhjung Janet Lee; Claudia Epland; Noah Kaitz; Olayinka Shiyanbola; Cody J. Wenthur (Scientific Reports)
Abstract Psychedelic clinical study environments are frequently visually manipulated, such as art; however, there has been little study of how the art selected for display impacts individual responses to the overall setting. To examine how individual self-identities shape perceptions of art used in a clinical psychedelic dosing environment, this study used a community-engaged mixed-methods approach. Psychedelic society members were recruited to complete an online survey that measured overall reactions and perceived connections of age, gender, racial/ethnic, and religious/spiritual self-identities to 15 art objects. A multivariate-linear regression model of these responses identified religious/spiritual identity as the dominant connectivity factor influencing art reaction among these participants. Selected survey participants then completed focus groups, from which nine qualitative themes related to art preferences were identified, including preference for natural elements and images. Finally, members of a non-psychedelically oriented community interest group completed the survey and provided preference scores for an expanded art library to assess generalizability of qualitative and quantitative findings. Spiritual/religious connectivity was found to be less associated with art preferences for the non-psychedelically affiliated group members, while the presence of natural elements still corresponded with positive responses to art. These results suggest that while religious/spiritual self-identity has a strong impact in predicting variance in dosing environment reactions among individuals with prior psychedelic interests, the inclusion of art focused on natural themes may be a meaningful future approach to facilitate positive receptions among broader populations.